Community-managed disaster risk reduction in drought and conflict affected areas of Ethiopia: Early warning and anticipatory action lessons and experiences from the CLAP /HoA consortium - Nielsen, Jannie; Tilahun, Markos; Awano, Zerihun; Getachew, Radwan (ADRA Denmark, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025